Confined compressive behaviors of high-performance fiber-reinforced concrete and conventional concrete with size effect. (20th June 2022) - Nguyen, Duy-Liem; Thai, Duc-Kien; Tran, Ngoc-Thanh; Ngo, Tri-Thuong; Le, Huy-Viet
Highlights: Exploring the size effect on confined compressive behavior of high-performance fiber-reinforced concrete (HPFRC) and conventional concrete (CC) using uPVC/steel cover. Evaluating the significances of such size effect based on the size effect laws of Weibull and Bažant. Correlating the axial compressive strength according to lateral strength of the HPFRC cores based on the Johnston's failure criteria. Abstract: In this article paper, the specimens' size effect on passively confined compressive behavior of high-performance fiber-reinforced concrete (HPFRC) and conventional concrete (CC) were investigated through an experimental test program. All compressive specimens were cylinder-shaped using steel/uPVC cover and HPFRC/CC core. The thicknesses of uPVC covers were 0, 3.2, and 3.8 mm while those of steel covers were 0, 1.4, and 1.8 mm. For the size effect of HPFRC, three different heights were designed to prepare specimens, which are 200, 400, and 600 mm with the same inner diameter of 114 mm. For the size effect of CC, the different-sized specimens were employed diversified by the heights of 200 and 600 mm with the same inner diameter of 114 mm. The specimens were subjected to compressive loading at the only concrete core and their engineering relationships between stress and strain were performed. The specimens with a thicker cover generally produced a higher compressive strength compared to the specimens that have the same dimensions as the covered ones, regardless of a concrete type. The effect of specimen height on confined compressive strength could be obviously observed for both HPFRC and CC. For HPFRC series, the unconfined HPFRC specimens produced the lower significance of size effect than the confined. The steel covers were more effective than uPVC covers for confinement of HPFRC cores in enhancing strength. Asides from those, the effect of confinement on compressive strength was also analytically analyzed and discussed through Johnston's failure criterion as well as the size effect laws of Weibull and Bažant.